Delivering desistance-focused probation in community hubs: Five key ingredients. (September 2020) - Phillips, Jake; Albertson, Kathy; Collinson, Beth; Fowler, Andrew
This article argues that probation is well placed to facilitate desistance when delivered in community hubs – community-based offices where probation services are co-located with other community-based provision. However, we highlight that hubs need to include certain key factors to maximise the potential for desistance. Using data collected through a piece of empirical research in six community hubs in England and Wales, we identify what factors make for a 'good' community hub as perceived by staff who work in them, those subject to supervision via a hub, and managers with strategic responsibility for commissioning hub services. We consider what it is about those factors which facilitate desistance-focused practice as outlined in McNeill et al.'s (2012) eight principles of desistance-focused practice. The five key factors identified in this study are the location of a hub, the hub's physical environment, the extent to which services are co-located/produced, the cultural context of the hub, and the need for leaders to be innovative in the way services are commissioned. The article concludes with a discussion of the implications for the National Probation Service as it takes over the work of Community Rehabilitation Companies in the coming years.